QUALITY ASSURANCE SYSTEMS IN PUBLIC TRANSPORT - Loksova, Zuzana (Doprava a spoje, 2012)
transport is out-sourced the quality of service has to be assured for obvious reasons. Therefore some relevant quality matters are presented in this article.